Distribution of Renal Histopathology in Guilan: a Single-center Report (Iranian Journal of Kidney Diseases, 2012)
Introduction. Glomerulonephritis is the third most common cause of end-stage renal disease. Epidemiological data of kidney disease is population-based and has great geographic variability. The aim of this study was to assess the results of all kidney biopsies in a 5-year period in the Guilan province. Materials and Methods. In a retrospective study of 336 kidney biopsies recorded in the Department of Nephrology in Razi Hospital of Rasht, capital city of Guilan province, from August 2001 to September 2006, data consisting of age, gender, indication of kidney biopsy, and histopathological diagnosis were collected and analyzed. Results. A total of 336 kidney biopsies were reviewed (73.8% males; mean age, 40.12 ± 16.78 years). Nephritic syndrome (42.5%) and nephrotic syndrome (38.7%) were the most frequent indications of biopsy. Overall, pathologic examinations were indicative of glomerulonephritis in 272 (81.0%) biopsies and nonglomerular diseases in 64 (19.0%). The most common cause of secondary glomerulonephritis was lupus nephritis (82.6%). Focal and segmental glomerusclerosis (20.5%) was the most common pathologic diagnosis, followed by membranous glomerulonephritis (14.9%), minimal change disease (11.6%), tubulointerstitial nephritis (8.9%), and IgA nephropathy (3.6%). The most common pathologic finding among glomerular diseases was focal segmental glomerusclerosis (25.4%), while tubulointerstitial nephritis (46.9%) was the most common among nonglomerular diseases, followed by diffuse glomerulosclerosis, interstitial fibrosis, and tubular atrophy indicative of end-stage renal disease (23.4%). Conclusions. In our study, FSGS was the most common pathologic finding in kidney biopsies, and the frequency of IgA nephropathy was much lower than that in other studies.